Maintaining the Firm’s Performance Stability of Indonesia’s Small to Medium Enterprises (SMEs): RBV and CSV Perspective - I Gusti Agung Musa Budidarma (East Asian Journal of Multidisciplinary Research, 2022)
The objective of this paper is to discuss the theoretical approach to pursuing firm performance stability by integrating RBV and CSV. This paper provides a literature review of RBV theory and CSV theory. Based on the theory, RBV and CSV might lead the firm to achieve a competitive advantage. The competitive advantages are superior firm resources compared to a competitor and the increasing of productivity. As a consequence, the firm's stable performance could be achieved since the firm generates more revenue, lowers costs, and then increases profit. This paper also has the managerial implication that the CSV mindset trains the manager’s attention on opportunities to take on societal and environmental challenges in innovative ways.